GIS-Based Land Capability for Settlements Area in Piyungan, Yogyakarta (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The development of the areas for settlement needs to be performed to meet the needs of the land. Research on the characteristics of engineering geology as a basis for determining the capability of land for settlements. The bearing capacity of rocks is based on the Geological Strength Index (GSI) rock mass classification, while the bearing capacity of soils is based on Dynamic Cone Penetration (DCP). Bearing capacity of the research areas, consisting of: sandstone 135 tons/m2, lapilli tuff 135 tons/m2, tuffaceous sandstone 45 tons/m2, andesite breccia 45 tons/m2, sand deposits 11-35 tons/m2, and silty clay deposits 6,5-8,6 tons/m2 with a liquid limit of 27-32,3%, and plastic index of 7,25-10,2%. Zoning of land capability is conducted using the Analytical Hierarchy Process (AHP) with criteria of bearing capacity, excavatability assessment, depth of groundwater level, slope, and geological disaster vulnerability. The land capability zone in the research areas consists of a high capability zone with an area of 33%, medium capability zone of 45%, and a low capability zone of 22% of the total research area in Piyungan, Yogyakarta.